2020
DOI: 10.36289/jtmi.v15i1.147
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Kajian ini bertujuan untuk mengetahui penyerapan air pada komposit resin poliester berpenguat serat agel tenun (Corypha gebanga) yang direndam dalam air distilasi dan larutan 3,5% NaCl. Bahan yang digunakan adalah serat agel tenun, resin poliester tak jenuh Yukalac 157 BQTN, dan katalis metil etil keton peroksida (MEKP). Teknik pembuatannya menggunakan vacuum bagging dengan tekanan hisap 70 cmHg pada suhu ruangan. Spesimen uji penyerapan air berdasarkan standar ASTM D570 selama 1080 jam pada suhu kamar. Hasil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…This structure can be clearly seen in the high magnification SEM micrograph (Figure 10d) of the OCF surface. Other studies also reported the micro changes of the fiber surface after alkali treatment [15,31], which are conducive to improving the interfacial adhesion between coir fiber and the polymer matrix. When the composites are produced, the fluid-like matrix material can enter the bumpy surface structure, and mechanical interlocking between the coir fiber and the polymer matrix can be produced after solidification, thus effectively improving the interfacial bonding performance between them [32,33].…”
Section: Scanning Electron Microscopy Observation and Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…This structure can be clearly seen in the high magnification SEM micrograph (Figure 10d) of the OCF surface. Other studies also reported the micro changes of the fiber surface after alkali treatment [15,31], which are conducive to improving the interfacial adhesion between coir fiber and the polymer matrix. When the composites are produced, the fluid-like matrix material can enter the bumpy surface structure, and mechanical interlocking between the coir fiber and the polymer matrix can be produced after solidification, thus effectively improving the interfacial bonding performance between them [32,33].…”
Section: Scanning Electron Microscopy Observation and Analysismentioning
confidence: 96%
“…The results showed that the tensile strength of alkali-treated and alkali-silanetreated fibers increased compared with untreated fibers, while that of silane-treated fibers decreased in comparison. In addition, the interfacial shear strength of the fibers treated in the above three ways rose compared with untreated ones [15]. Loong et al treated flax fiber with acetic anhydride to investigate the effect on the properties of flax fiber epoxy composites.…”
Section: Introductionmentioning
confidence: 99%
“…The free ends of the fibers in the specimens were carefully fixed on a mounting tap to obtain a calibrated length of 30 mm. A Shimadzu ® EZ-Test machine with a load cell of 100 N was used to perform the pull-out tests, and a crosshead speed of 5 mm/min was set [37]. The specimens were clamped with the fixed lower crosshead, and the fiber was pulled out with the movable upper crosshead.…”
Section: Pull-out Testmentioning
confidence: 99%
“…Banana pseudostem samples were cut vertically into thin strips and were dried in an oven at 100 ± 5 • C. They were then ground and sieved to obtain microfibers (MFs) [29]. To obtain microcrystalline cellulose (MCC), an alkaline stage and a bleaching stage were carried out [30]. The alkaline treatment was carried out with NaOH for 45 min at 75 • C under stirring, the MFs were washed after each alkaline treatment with distilled water.…”
Section: Cellulose Microcrystalline Isolationmentioning
confidence: 99%